Suicidal ideation and self-destructive behavior in Vietnamese adolescents and young adults with psychiatric disorders - Thi To Uyen Duong; Nguyen Ngoc Tran; Thi Anh Thoa Nguyen; Van Hai Nguyen; Lam Vu Tran; Van Thich Pham; Thu Ha Nguyen; Thi Thu Cao; My Ha Tran; Thanh Tung Pham; Le Tuan Linh Hoang; Danh Khai Duong (Discover Psychology)
Abstract Objective Suicide trends among adolescents aged 15–24 are often linked to significant life transitions, such as changes in living and working environments; however, in Vietnam, research on suicide in the general population remains limited. The aim of this study was to identify at-risk youth related to suicidal ideation and self-destructive behavior in adolescents and young adult psychiatric patients. Methods This study included 101 participants aged 15–24 receiving inpatient treatment at the Institute of Mental Health, Bach Mai Hospital, Vietnam between August 2021 and June 2022. The Columbia-Suicide Severity Rating Scale was used to assess suicidal ideation and behaviors. Logistic regression was used to calculate the odds ratio (OR) and 95% confidence intervals (95%CI) between risk factors and suicide ideation and self-destructive behavior. Results The prevalence of current ideation and self-destructive were 54.5% and 36.6%, respectively. The study suggests females had a higher OR of current suicidal ideation and self-destructive behavior than males (all p-values < 0.05). The results showed that a personal history of attempted suicide and current mental stress increased the odds of current suicidal ideation and self-destructive behavior (p < 0.05). Additionally, in the 15-19-year-old group, childhood traumas had a higher OR of self-destructive behavior (p-value = 0.029). In the 20-24-year-old group, treatment adherence had a lower OR of current suicidal ideation (p-value = 0.03). Conclusions This study suggested that gender, history of suicide attempts, and current mental stress were significantly associated with suicidal ideation and self-destructive behavior in adolescents and young adult psychiatric patients. Paying more attention to young patients with a history of attempted suicide and current mental stress, especially females, to prevent suicidal ideation and self-destructive behavior is needed.